Le cœur en sabot: shape associations with adverse events in repaired tetralogy of Fallot - Mîra, Anna; Lamata, Pablo; Pushparajah, Kuberan; Abraham, Georgina; Mauger, Charlène A.; McCulloch, Andrew D.; Omens, Jeffrey H.; Bissell, Malenka M.; Blair, Zach; Huffaker, Tyler; Tandon, Animesh; Engelhardt, Sandy; et al. (Journal of cardiovascular magnetic resonance, 2022)
Maladaptive remodelling mechanisms occur in patients with repaired tetralogy of Fallot (rToF) resulting in a cycle of metabolic and structural changes. Biventricular shape analysis may indicate mechanisms associated with adverse events independent of pulmonary regurgitant volume index (PRVI). We aimed to determine novel remodelling patterns associated with adverse events in patients with rToF using shape and function analysis.
Gesehen am 25.09.2022